Obstacles and Solutions in Implementing RADEC Learning Through Visual Media in Reading Comprehension Learning: Case Study in Class IV Elementary School - Nyolandra, Putri Rhamadyna; Syaodih, Ernawulan (International Conference on Elementary Education, 2025)
This research aims to identify obstacles and solutions in implementing the RADEC model withvisual media to help students understand reading in fourth grade elementary school. The method usedin this research is a qualitative approach with a case study design. Data was collected using interview,observation and documentation techniques. Based on interviews, teachers already understand theRADEC stages, there are challenges that must be faced at the Discuss and Create stages, especially in inviting students to discuss and understand the material. Visual media such as pictures, videos and graphics help students understand reading, but are hampered by device limitations and internet connections. Visual media also does not fully match students' learning styles, so teachers use various other media. Most students responded positively, especially in the Read and Answer stages, although there were difficulties in the Discuss and Create stages. To overcome this obstacle, teachers create simple visual media such as illustrations or mind maps and propose regular training and improvingschool facilities.